Social and Behaviour Change Communication Interventions in Mozambique - Cooper, Rachel (2019)
Social and behaviour change communication (SBCC) is the use of communication to change behaviours by positively influencing knowledge, attitudes and social norms at the individual and community level. Approaches to SBCC include, but are not limited to: media campaigns, peer educators and mentors, small group sessions, community dialogues and events, and digital tools. This rapid literature review focuses on SBCC interventions in Mozambique across four sectors: family planning (FP); girls’ empowerment; water, sanitation and hygiene (WASH), and nutrition. The most common SBCC approaches across the four sectors include: Inter-personal communication, Community participatory approaches, SMS based platforms, and Media channels. This review draws on evaluations of SBCC intervention, donor reports, and qualitative evidence collected by implementers and funders. There is a relatively large evidence base for FP and nutrition interventions, and a comparatively smaller one for WASH and girls’ empowerment. No lessons learned from integrating WASH and nutrition programming could be found during the course of this review. Although there are examples of nutrition programming including WASH in their counselling interventions, as well as calls for the development of multisectoral programmes. For example, in 2017, UNICEF signed a multi-sectoral proposal covering WASH, nutrition, and behaviour change funded by the EU. The programme will work in Nampula and Zambezia Provinces between 2017 and 2021.
Accepted: 2020-02-14T13:40:55Z Publisher: IDS
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; health / saúde; ⛔ No DOI found

Democratization of Health Services: Dynamics of Administrative Resistances (N'weti - comunicação para saúde, 2019)
This policy brief, apart from describing the dilemmas of the democratization process of health services it, aims to analyze its implications on the dynamics of social accountability in the health sector and, finally, to inform on possible ways for a more coherent democratization, considering the normative discourses
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; decentralization / descentralização; health / saúde

Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique - Khadiagala, Gilbert M.; Manhique, Jorge R. (WFD - Moçambique, 2019)
The inclusion of persons with disabilities is an essential element of a strong democracy and a just society. Persons with disabilities (PWDs) being included means that they have a full and equal opportunity to participate in society and in political decision-making processes, to develop their capacities, and to contribute to national progress Like everywhere, persons with disabilities in Mozambique face physical, social, economic and/or environmental barriers to participation. For example, 17 percent of persons with disabilities in Mozambique have been refused entry into a school or preschool because of their disability. Prior to its ratification of the International Convention on the Rights of People with Disability (ICCPD), which protects and promotes the rights and dignity of persons with disabilities, Mozambique had already pioneered progressive measures to promote the inclusion of persons with disability through specific principles in the Constitution of the Republic and the development of multisectoral plans on disability. Furthermore, the Mozambican Government proposed a new set of commitments that were presented at the London Summit in July 2018, reaffirming its adherence to the International Convention on the Rights of People with Disability. The Mozambican Minister for Gender, Children and Social Action, Her Excellency Cidália Manuel Chaúque Oliveira, today spoke at an event on 18th December to launch the study, ‘Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique.’ The study is the result of consultations with people with disabilities of different types and other stakeholders working to promote the rights of persons with disabilities (PWDs) in the Nampula, Beira and Maputo regions of Mozambique. The consulations aimed to find out about the socio-economic and political situations of PWDs and the barriers they face, as well as propose solutions to those problems. The consultation is part of the effort to establish a National Agenda for greater social, economic and political inclusion of PWDs in Mozambique. The study identifies the opportunities for, progress made, obstacles to, and consensus on national policies and strategies. It articulates a ways forward for building an inclusive society and achieving social justice. The study contibutes to Mozambique’s efforts work effectively towards national and international commitments to inclusive development. The study was undertaken as part of the Commonwealth Partnership for Democracy (CP4D) programme. It was carried out by WFD Mozambique in partnership with the Mozambican Association of People with Disability (ADEMO), the Mozambican Forum of Associations for People with Disability (FAMOD), and the Assembly of the Republic of Mozambique, in collaboration with the Ministry of Gender, Children and Social Action and with the technical advice of the Centre for Human Rights of the University of Pretoria in South Africa.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 - INS; ICF (INS/Mozambique, INE, PNCM, ICF, 2019)
O presente relatório resume os resultados do Inquérito Nacional sobre Indicadores de Malária em Moçambique, conduzido pelo Instituto Nacional de Saúde (INS), em colaboração com o Programa Nacional de Controlo da Malária (PNCM) e o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através The Demographic and Health Surveys (DHS) Program. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos Contra a Malária (PMI) e o Fundo das Nações Unidas para a Infância (UNICEF).
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Midwives’ perspectives on (dis)respectful intrapartum care during facility-based delivery in sub-Saharan Africa: a qualitative systematic review and meta-synthesis - Bradley, Susan; McCourt, Christine; Rayment, Juliet; Parmar, Divya (Reproductive Health, 2019)
Background: In the past decade, the negative impact of disrespectful maternity care on women’s utilisation and experiences of facility-based delivery has been well documented. Less is known about midwives’ perspectives on these labour ward dynamics. Yet efforts to provide care that satisfies women’s psycho-socio-cultural needs rest on midwives’ capacity and willingness to provide it. We performed a systematic review of the emerging literature documenting midwives’ perspectives to explore the broader drivers of (dis)respectful care during facility-based delivery in the sub-Saharan African context. Methods: Seven databases (CINAHL, PsychINFO, PsychArticles, Embase, Global Health, Maternity and Infant Care and PubMed) were systematically searched from 1990 to May 2018. Primary qualitative studies with a substantial focus on the interpersonal aspects of care were eligible if they captured midwives’ voices and perspectives. Study quality was independently assessed by two reviewers and PRISMA guidelines were followed. The results and findings from each study were synthesised using an existing conceptual framework of the drivers of disrespectful care. Results: Eleven papers from six countries were included and six main themes were identified. ‘Power and control’ and ‘Maintaining midwives’ status’ reflected midwives’ focus on the micro-level interactions of the mother-midwife dyad. Meso-level drivers of disrespectful care were: the constraints of the ‘Work environment and resources’; concerns about ‘Midwives’ position in the health systems hierarchy’; and the impact of ‘Midwives’ conceptualisations of respectful maternity care’. An emerging theme outlined the ‘Impact on midwives’ of (dis)respectful care. Conclusion: We used a theoretically informed conceptual framework to move beyond the micro-level and interrogate the social, cultural and historical factors that underpin (dis)respectful care. Controlling women was a key theme, echoing women’s experiences, but midwives paid less attention to the social inequalities that distress women. The synthesis highlighted midwives’ low status in the health system hierarchy, while organisational cultures of blame and a lack of consideration for them as professionals effectively constitute disrespect and abuse of these health workers. Broader, interdisciplinary perspectives on the wider drivers of midwives’ disrespectful attitudes and behaviours are crucial if efforts to improve the maternity care environment - for women and midwives - are to succeed.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Religion and Use of Institutional Child Delivery Services: Individual and Contextual Pathways in Mozambique - Cau, Boaventura Manuel; Agadjanian, Victor (International perspectives on sexual and reproductive health, 2019)
CONTEXT: Research on institutional child delivery in Sub-Saharan Africa typically focuses on availability and accessibility of health facilities. Cultural factors, including religion, that may facilitate or hinder the use of such services have not been well examined and remain poorly understood. METHODS: The relationship between religious affiliation and delivery in a health facility was explored using data from a household survey of 1,297 women aged 18-50 and a census of 825 religious congregations, both conducted in a predominantly Christian district in Mozambique in 2008. Multilevel logistic regression analyses were conducted to predict the likelihood of recent institutional delivery according to both individual religious affiliation and the concentration of religious congregations of certain denominations in the community of residence. RESULTS: Approximately 63% of deliveries occurred in a health facility. The odds of such deliveries were lower among women who belonged to Apostolic churches or had no religious affiliation than among members of Catholic or mainline Protestant churches, net of other factors (odds ratios, 0.5 and 0.6, respectively). In addition, regardless of a woman's religion, the odds that she had an institutional delivery increased by 9% for each additional Catholic or mainline Protestant congregation in her community of residence (1.1). CONCLUSIONS: Organized religion is associated with critical health outcomes in Mozambique and, potentially, in other Sub-Saharan African contexts. Policymakers should consider designing programs and interventions that promote the use of institutional delivery services among members of religious groups characterized by low use of these services and in areas where such religious groups have a strong presence.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Disrespect and abuse during facility-based childbirth in southern Mozambique: a cross-sectional study - Galle, Anna; Manaharlal, Helma; Cumbane, Emidio; Picardo, Joelma; Griffin, Sally; Osman, Nafissa; Roelens, Kristien; Degomme, Olivier (BMC Pregnancy and Childbirth, 2019)
Evidence suggests that many women experience mistreatment during childbirth in health facilities across the world, but the magnitude of the problem is unknown. The occurrence of disrespect and abuse (D&A) in maternity care services affects the overall quality of care and may undermine women’s trust in the health system. Studies about the occurrence of disrespect and abuse in Mozambican health facilities are scarce. The aim of this study was to explore the experience of women giving birth in hospital in different settings in Maputo City and Province, Mozambique.
Keywords: G - Mozambique / Moçambique; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Health equity monitoring is essential in public health: lessons from Mozambique - Llop-Gironés, Alba; Cash-Gibson, Lucinda; Chicumbe, Sergio; Alvarez, Francesc; Zahinos, Ivan; Mazive, Elisio; Benach, Joan (Globalization and Health, 2019)
Background: Countries must be able to describe and monitor their populations health and well-being needs in an attempt to understand and address them. The Sustainable Development Goals (SDGs) have re-emphasized the need to invest in comprehensive health information systems to monitor progress towards health equity; however, knowledge on the capacity of health information systems to be able do this, particularly in low-income countries, remains very limited. As a case study, we aimed to evaluate the current capacity of the national health information systems in Mozambique, and the available indicators to monitor health inequalities, in line with SDG 3 (Good Health and Well Being for All at All Ages). Methods: A data source mapping of the health information system in Mozambique was conducted. We followed the World Health Organization’s methodology of assessing data sources to evaluate the information available for every equity stratifier using a three-point scale: 1 - information is available, 2 - need for more information, and 3 an information gap. Also, for each indicator we estimated the national average inequality score. Results: Eight data sources contain health information to measure and monitor progress towards health equity in line with the 27 SDG3 indicators. Seven indicators bear information with nationally funded data sources, ten with data sources externally funded, and ten indicators either lack information or it does not applicable for the matter of the study. None of the 27 indicators associated with SDG3 can be fully disaggregated by equity stratifiers; they either lack some information (15 indicators) or do not have information at all (nine indicators). The indicators that contain more information are related to maternal and child health. Conclusions: There are important information gaps in Mozambique’s current national health information system which prevents it from being able to comprehensively measure and monitor health equity. Comprehensive national health information systems are an essential public health need. Significant policy and political challenges must also be addressed to ensure effective interventions and action towards health equity in the country.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - health information systems / saúde - sistema de informação de saúde; health - maternal and child / saúde - materno-infantil; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde

Demand-side financing in the form of baby packages in Northern Mozambique: Results from an observational study - Makins, Anita; Ehmer, Jochen; Piprek, Alexandra; Mbofana, Francisco; Ross, Amanda; Hobbins, Michael André (PLOS ONE, 2019)
Background The Maternal Mortality Ratio in Mozambique has stagnated at 405 deaths per 100,000 live births with virtually no progress over the last 15 years. Low Institutional Birth Rates (IBRs) levelling around 50% in many rural areas constitute one of the contributing reasons. Demand-side financing has successfully increased usage of maternal health services in other countries, but little information exists on in-kind incentives in rural Africa. The objective was to test the impact on Institutional Birth Rates of giving a USD 5.50 baby package incentive to every woman who came to give birth in a health centre in a rural, poor district of Cabo Delgado, Mozambique. Methods and findings The intervention was implemented in one district in 2010 with the remaining 15 districts serving as controls. The total population in the 16 districts in 2006 was just under 1.5 million people. IBRs were observed from 2006 to 2013 (53 months before and 55 months after the intervention began). The non-intervention districts showed a slight increase, from a mean IBR of 0.39 (SD = 0.10) in 2006 to 0.67 (SD = 0.13) in 2014. The intervention district had a dramatic increase in IBRs within six months of the start of the intervention in 2010, which was sustained until the end of the study. Adjusting for the background increase and for confounders, including health facilities and health personnel per district, and taking clustering in districts into account, the estimated rate ratio of institutional births in the intervention district was 1.80 (95% CI 1.72, 1.89 p<0.001). Conclusion Women were almost twice as likely to have an institutional birth following the introduction of the baby package.
Publisher: Public Library of Science
Keywords: G - Mozambique / Moçambique; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

The Health Budget: The Disparity Between Political Discourse and Practice - N'weti (N'weti, 2019)
Key Messages: - Health is a human right and is constitutionally protected in Mozambique; - The health sector is considered a priority sector by the Government of Mozambique; - The health sector is amongst the least funded by the State Budget in the past four years, (with less than 8% on average), against the 15% assumed in Abuja; - For the year 2014, of the 762.8 million USD allocated to the health sector, 44% came from external sources (REO MOH, 2014). The combined PROSAUDE resources, and the speci c "off-budget" projects’ funding demonstrates the enormous reliance on external partners to support the country’s health strategy; - There is an urgent need to increase internal State Budget funding for the health sector to ensure sustainability.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; budget / orçamento; health / saúde

Obstacles to advancing women’s health in Mozambique: a qualitative investigation into the perspectives of policy makers - Qiu, Mary; Sawadogo-Lewis, Talata; Ngale, Katia; Cane, Réka Maulide; Magaço, Amilcar; Roberton, Timothy (Global Health Research and Policy, 2019)
Background: Despite substantial investment in women’s health over the past two decades, and enthusiastic government support for MDG 5 and SDG 3, health indicators for women in Mozambique remain among the lowest in the world. Maternal mortality stayed constant from 2003 to 2011, with an MMR of 408; the estimated HIV prevalence for women of 15–24 years is over twice that for men; and only 12.1% of women are estimated to be using modern contraception. This study explores the perspectives of policy makers in the Mozambican health system and affiliates on the challenges that are preventing Mozambique from achieving greater gains in women’s health. Methods: We conducted in-depth interviews with 39 senior- and mid-level policy makers in the Ministry of Health and affiliated institutions (32 women, 7 men). Participants were sampled using a combination of systematic random sampling and snowball sampling. Participants were asked about their experiences formulating and implementing health policies and programs, what is needed to improve women’s health in Mozambique, and the barriers and opportunities to achieving such improvement. Results: Participants unanimously argued that women’s health is already sufficiently prioritized in national health policies and strategies in Mozambique; the problem, rather, is the implementation and execution of existing women’s health policies and programs. Participants raised challenges related to the policy making process itself, including an ever-changing, fragmented decision-making process, lack of long-term perspective, weak evaluation, and misalignment of programs across sectors. The disproportionate influence of donors was also mentioned, with lack of ownership, rapid transitions, and vertical programming limiting the scope for meaningful change. Finally, participants reported a disconnect between policy makers at the national level and realities on the ground, with poor dissemination of strategies, limited district resources, and poor consideration of local cultural contexts. Conclusions: To achieve meaningful gains in women’s health in Mozambique, more focus must be placed on resolving the bottleneck that is the implementation of existing policies. Barriers to implementation exist across multiple health systems components, therefore, solutions to address them must also reach across these multiple components. A holistic approach to strengthening the health system across multiple sectors and at multiple levels is needed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Impacto das Uniões Prematuras na Educação, Saúde e Nutrição em Moçambique: Resumo do Documento - ROSC (ROSC - F;orum da Sociedade Civil para os Direitos da Criança, 2019)
As uniões prematuras constituem um dos principais problemas sociais na África Austral que, pelas suas consequências negativas em cadeia: gravidez precoce,desnutrição crónica,fístula obstétrica,abandono escolar,se tornam um problema igualmente económico, uma barreira ao desenvolvimento socioeconómico. No caso de Moçambique, o problema afecta cerca de metade das raparigas com menos de 18 anos, o que faz do país um dos cinco mais afectados a nível da Comunidade dos Países da África Austral (SADC). Para fazer face a este problema, várias acções têm sido levadas a cabo, entre campanhas de sensibilização, programas de resgate de meninas em situação de vida marital precoce, lobby e advocacia para o fortalecimento do quadro institucional e legal, bem como estudos para melhor informar as acções referidas. No entanto, quase todas as pesquisas feitas à volta das uniões prematuras têm sido na perspectiva sociológica ou antropológica. Por isso, o Fórum da Sociedade Civil para os Direitos da Criança (ROSC), no âmbito das acções da Coligação para a Eliminação dos Casamentos Prematuros (CECAP), com o apoio da OXFAM, através do Programa AGIR, decidiu realizar este estudo de perspectiva económica, para aferir o impacto que as uniões prematuras têm na educação, saúde e nutrição no país. Este estudo foi elaborado com quatro finalidades: primeira, contribuir para o debate sobre o impacto das uniões prematuras; segunda, elucidar aos actores-chave sobre as consequências das uniões prematuras para o desenvolvimento do país; terceira, despertar a consciência dos tomadores de decisão e da sociedade no geral sobre os impactos negativos das uniões prematuras na educação, saúde e nutrição; quarta e última finalidade, contribuir para despertar a atenção para a necessidade do desenho de programas, políticas e leis que visam mitigar os impactos negativos das uniões prematuras
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género; health / saúde

Introduction: The Accountability Politics of Reducing Health Inequalities: Learning from Brazil and Mozambique - Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P.; Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P. (Novos estudos CEBRAP, 2019)
Inequality is a key political issue of our times. It has political consequences, fuelling conflict and raising legitimacy chal‑ lenges for regimes around the world, in democratic and non‑demo‑ cratic settings alike. At the centre of these challenges is the question of accountability: who can be held accountable, on what basis, how and by whom for tackling or failing to tackle which inequalities. In the field of global health, inequality has long been a key issue. A significant body of work — in global health and health systems research — has approached the issue of health inequalities and in‑ equities by highlighting the role of social determinants (Marmot, 2015; Wilkinson; Pickett, 2006; Barreto, 2017). A more recent and less developed stream of work frames them in terms of political de‑ terminants: in other words, seeing them as issues that may be ad‑ dressed through politics as well as policy.
Publisher: Centro Brasileiro de Análise e Planejamento
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde

Rethinking health accountability in Mozambique: Beyond donors and government? (Institute of Development Studies, 2018)
As I explored in my previous blog, the health sector and provision of health services in Mozambique is an uneven playing field. Since 1980 it has been shaped by a range of donors who have strategically positioned themselves according to their political weight and ability to contribute with ‘commodities’ and financial resources. Although donors’ contributions […]
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; health / saúde

When a health system turns into a Tower of Babel: Mozambique's experience - Namburete, Denise (Institute of Development Studies, 2018)
Likened to the Tower of Babel legend, the Mozambican national health system speaks several languages and pursues a range of different interests, answering to a number of partners and other bilateral and multilateral actors who all have some kind of circumstantial and contextual interest. When the Paris Declaration on Aid Effectiveness was endorsed, Mozambique may […]
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde

Progress in Mozambique: Changes in the availability, use, and quality of emergency obstetric and newborn care between 2007 and 2012 - Augusto, Orvalho; Keyes, Emily E.; Madede, Tavares; Abacassamo, Fátima; de la Corte, Pilar; Chilundo, Baltazar; Bailey, Patricia E. (PLOS ONE, 2018)
Introduction Maternal mortality in Mozambique has not declined significantly in the last 10–15 years, plateauing around 480 maternal deaths per 100,000 live births. Good quality antenatal care and routine and emergency intrapartum care are critical to reducing preventable maternal and newborn deaths. Materials and methods We compare the findings from two national cross-sectional facility-based assessments conducted in 2007 and 2012. Both were designed to measure the availability, use and quality of emergency obstetric and neonatal care. Indicators for monitoring emergency obstetric care were used as were descriptive statistics. Results The availability of facilities providing the full range of obstetric life-saving procedures (signal functions) decreased. However, an expansion in the provision of individual signal functions was highly visible in health centers and health posts, but in hospitals, performance was less satisfactory, with proportionally fewer hospitals providing assisted vaginal delivery, obstetric surgery and blood transfusions. All other key indicators showed signs of improvements: the institutional delivery rate, the cesarean delivery rate, met need for emergency obstetric care (EmOC), institutional stillbirth and early neonatal death rates, and cause-specific case fatality rates (CFRs). CFRs for most major obstetric complications declined between 17% and 69%. The contribution of direct causes to maternal deaths decreased while the proportion of indirect causes doubled during the five-year interval. Conclusions The indicator of EmOC service availability, often used for planning and developing EmONC networks, requires close examination. The standard definition can mask programmatic weaknesses and thus, fails to inform decision makers of what to target. In this case, the decline in the use of assisted vaginal delivery explained much of the difference in this indicator between the two surveys, as did faltering hospital performance. Despite this backsliding, many signs of improvement were also observed in this 5-year period, but indicator levels continue below recommended thresholds. The quality of intrapartum care and the adverse consequences from infectious diseases during pregnancy point to priority areas for programmatic improvement.
Publisher: Public Library of Science
Keywords: G - Mozambique / Moçambique; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

‘When helpers hurt’: women’s and midwives’ stories of obstetric violence in state health institutions, Colombo district, Sri Lanka - Perera, Dinusha; Lund, Ragnhild; Swahnberg, Katarina; Schei, Berit; Infanti, Jennifer J.; Darj, Elisabeth; Lukasse, Mirjam; Bjørngaard, Johan Håkon; Joshi, Sunil Kumar; Rishal, Poonam; Koju, Rajendra; Pun, Kunta Devi; et al. (BMC Pregnancy and Childbirth, 2018)
The paper explores how age, social position or class, and linguistic and cultural background intersect and place women in varying positions of control and vulnerability to obstetric violence in state health institutions in Colombo district, Sri Lanka. Obstetric violence occurs during pregnancy, childbirth and the immediate postpartum period; hence, it is violence that directly affects women. The authors aim to break the traditional culture of silence around obstetric violence and bring attention to the resulting implications for quality of care and patient trust in obstetric care facilities or providers.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
978-1-78118-441-7
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Inverted State and Citizens’ Roles in the Mozambican Health Sector - Dias, Jose; Tomé, Tassiana (IDS Bulletin, 2018)
This article aims to understand the inversion of roles between the state and citizens, by exploring its historical roots and current implications for processes of social accountability in Mozambique, particularly in the health sector. This is a practice-based reflection grounded in the evidence collected through the implementation of Community Scorecards in the health sector in 13 districts of Mozambique. The evidence has revealed a transfer of responsibilities from local governance institutions and service providers to the communities; diluting the frontiers between the state and citizens’ duties and rights, resulting in the inversion of roles. This inversion results in the minimisation of the state’s performance of its duties and accountability in the health sector to respond to local communities’ needs, allegedly due to the lack of financial resources. It also leads to the overburdening of local communities, who assume the responsibility of meeting their own demands, risking participation fatigue.
Accepted: 2018-05-01T10:02:21Z Publisher: Institute of Development Studies
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; Important; L - english / inglês; Northern PEA; accountability / responsabilização; health / saúde

New Action Plan for Health Promotion in Cabo Delgado (Mozambique) (2018)
In Cabo Delgado - Mozambique, we are giving support to the Provincial Health Directorate (DPS-CD) in developing an essential tool for the promotion of health in the Province: The Action Plan for Health Promotion.
Keywords: *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; health / saúde

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Disrespectful and abusive treatment during facility delivery in Tanzania: a facility and community survey - Kruk, Margaret E; Kujawski, Stephanie; Mbaruku, Godfrey; Ramsey, Kate; Moyo, Wema; Freedman, Lynn P (Health Policy and Planning, 2018)
Although qualitative studies have raised attention to humiliating treatment of women during labour and delivery, there are no reliable estimates of the prevalence of disrespectful and abusive treatment in health facilities. We measured the frequency of reported abusive experiences during facility childbirth in eight health facilities in Tanzania and examined associated factors. The study was conducted in rural northeastern Tanzania. Using a structured questionnaire, we interviewed women who had delivered in health facilities upon discharge and re-interviewed a randomly selected subset 5–10 weeks later in the community. We calculated frequencies of 14 abusive experiences and the prevalence of any disrespect/abuse. We performed logistic regression to analyse associations between abusive treatment and individual and birth experience characteristics. A total of 1779 women participated in the exit survey (70.6% response rate) and 593 were re-interviewed at home (75.8% response rate). The frequency of any abusive or disrespectful treatment during childbirth was 343 (19.48%) in the exit sample and 167 (28.21%) in the follow-up sample; the difference may be due to courtesy bias in exit interviews. The most common events reported on follow-up were being ignored (N = 84, 14.24%), being shouted at (N = 78, 13.18%) and receiving negative or threatening comments (N = 68, 11.54%). Thirty women (5.1%) were slapped or pinched and 31 women (5.31%) delivered alone. In the follow-up sample women with secondary education were more likely to report abusive treatment (odds ratio (OR) 1.48, confidence interval (CI): 1.10–1.98), as were poor women (OR 1.80, CI: 1.31–2.47) and women with self-reported depression in the previous year (OR 1.62, CI: 1.23–2.14). Between 19% and 28% of women in eight facilities in northeastern Tanzania experienced disrespectful and/or abusive treatment from health providers during childbirth. This is a health system crisis that requires urgent solutions both to ensure women’s right to dignity in health care and to improve effective utilization of facilities for childbirth in order to reduce maternal mortality.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde

GFF Civil Society Engagement Strategy Addendum - Adolescent and Youth (AY) - Global Financing Facility (Global Financing Facility, 2018)
The Global Strategy for Women’s, Children’s and Adolescents’ Health 2016-30 highlights the importance of adolescent health and well-being as being essential to achieving the Sustainable Development Goals (SDG) by 2030. For adolescents to survive, thrive and transform their societies, the global community needs to invest in their health and well-being. Today’s adolescents are well-positioned to mobilize their peers, advocate for increased resources for sexual and reproductive health and rights, influence their governments to invest in addressing their needs, and demand accountability for commitments related to their health and development. The Global Financing Facility (GFF) Civil Society Engagement Strategy (CSES) and related implementation plan provide a clear framework for civil society organizations’ (CSOs) contribution to the improvement of health outcomes through coalition strengthening, meaningful participation in multi-stakeholder country platforms responsible for coordinating health plans and their implementation,1 and coordinated action in support of the achievement of national sexual, reproductive, maternal, newborn, child and adolescent health (SRMNCAH) goals. Youth and adolescent led organizations should use the CSES as the basis for their engagement in the GFF processes both at the global and national levels. This Adolescent and Youth (AY) addendum to the CSES outlines a deliberate approach to ensuring youth representation in the processes led by the GFF Civil Society Coordinating Group2 (CSCG) to ensure their meaningful and active participation in the design, implementation, monitoring and evaluation of their country investment case.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; development partners / parceiros de cooperação; health / saúde; youth / juventude

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 Folheto (Brochure) - INS (2018)
O objectivo do IIM 2018 é disponibilizar as estimativas de indicadores demográficos e de saúde básicos, relacionados com a malária. As informações recolhidas através do IIM 2018 destinam-se a ajudar os decisores políticos e gestores do programa de controle de malária na avaliação e concepção de estratégias para melhorar a saúde da população do país.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA) 2015 - Ministério da Saúde- MISAU; Instituto Nacional de Estatística - INE; ICF (MISAU/Moçambique, INE, and ICF, 2018)
O presente relatório resume os resultados do Inquérito de Indicadores de Imunização, Malária e HIV/SIDA em Moçambique (IMASIDA 2015), conduzido pelo Instituto Nacional de Saúde (INS) do Ministério da Saúde (MISAU), em colaboração com o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através do Programa de Inquéritos Demográficos e de Saúde (Programa DHS). A assistência técnica adicional foi proporcionada pelo CDC (Centers for Disease Control and Prevention) dos Estados Unidos da América, através do seu escritório em Moçambique. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos para o Controlo da Malária (PMI), Fundo Global (FG-Rondas 8 e 9), Organização Mundial de Saúde (OMS), Fundo das Nações Unidas para a Infância (UNICEF), Aliança Internacional para a Saúde/Universidade de Washington (HAI/UW), Fundo das Nações Unidas para a População (FNUAP), Conselho Nacional de Combate ao HIV e SIDA (CNCS), através do seu Fundo Comum e Plano de Emergência do Presidente dos Estados Unidos para o Alívio da SIDA (PEPFAR), através do CDC.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Fast Facts from the 2018 Mozambique MIS - The DHS Program (2018)
The 2018 Mozambique Malaria Indicator Survey (IIM) provides population-based estimates on malaria indicators to inform strategic planning and program evaluation. The 2018 LMIS is the 6th survey to be conducted in Mozambique through The DHS Program.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Cidadania e Mudanças na Saúde e Educação em Moçambique: O Cartão de Pontuação Comunitária - Franco, Erika Lopez; Citizen Engagement Programme (CEP) (2017)
Este documento sumariza as aprendizagens feitas ao longo da implementação do Cartão de Pontuação Comunitária (CPC) no quadro do Programa Cidadania e Participação (CEP), o qual terminou em Dezembro de 2017. O CEP foi um programa de responsabilização social que tinha como objectivo final aumentar a influência dos cidadãos na melhoria da qualidade dos serviços de saúde e educação em Moçambique.
Accepted: 2018-04-13T12:59:17Z Publisher: (CEP) Citizen Engagement Programme / Cidadania e Participação
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; Northern PEA; access to services / acesso a serviços; citizenship & participation / cidadania e participação; community scorecard (CSC) / cartão de pontuação comunitária (CPC); education / educação; health / saúde

GFF Implementation Plan for the Gff Civil Society Engagment Strategy - Global Financing Facility (Global Financing Facility, 2017)
The implementation plan for the civil society engagement strategy (CSES) is developed to provide civil society organizations in countries (CSOs) with an operational framework to strengthen their engagement in the GFF process with a view to supporting the achievement of the objectives of the GFF and national investment cases. The plan reflects and builds on, and should be read in conjunction with the CSES. It is shaped and informed by GFF country implementation experiences to date, 12345 as well as the results of a targeted 2017 survey sent to CSOs working in GFF countries. The survey was geared towards understanding: 1) the civil society landscape in countries; 2) the level of knowledge of the GFF processes by CS; 3) priority actions CS can take to strengthen their engagement in the GFF processes and to support the achievement of the RMNCAH investment cases; and 4) what resources CS might need to better engage with national platforms and planning processes and to implement the identified supportive actions. The survey was sent to 18 organizations in 12 GFF countries and had a 61% response rate.
Sixth Invertors Group Meeting
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; health / saúde

An exploratory study of men’s companionship, perceptions and experiences during pregnancy and delivery in Uganda - Lwanga, H.; Atuyambe, L.; Sempewo, H.; Lumala, A.; Byaruhanga, R. N. B. (BMC Pregnancy and Childbirth, 2017)
Globally, low involvement of men in maternal health care services remains a problem to health care providers and policy makers. Men’s support is essential for making women’s world better. There are increasing debates among policymakers and researchers on the role of men in maternal health programs, which is a challenge in patriarchal societies like Uganda. The aim of the study was to assess companionship during delivery; men’s perception and experiences during pregnancy and delivery.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Maternal and Newborn Mortality: Community Opinions on Why Pregnant Women and Newborns Are Dying In Natikiri, Mozambique - Belo, C; Pires, P; Josaphat, J; Siemens, R; Rooke, E; Spence-Gress, C (International Journal of Research, 2017)
Background and objective: maternal and neonatal mortality rates in Mozambique are high, due to insufficient numbers of qualified health workers, lack of equipment and materials, referral system deficiency, difficulties to access health services and gender issues. This study assesses the barriers to health care access, regular attendance at ante natal consultations, institutional delivery and postnatal and neonatal follow-up. This is part of the baseline study for an implementation research project to reduce maternal and neonatal mortality in Natikiri, Nampula, Mozambique. Conclusion: local community members and health professionals were asked to state what they thought would be the best way to intervene. These ideas were then discussed further at a conference with health professionals and government representatives. Six intervention strategies to address identified problems were decided on and will be the basis for the ongoing implementation research project. They were: 1. Expanding family planning especially with adolescents. 2. Community based transport system for pregnant women. 3. Strengthening maternal and child health services by training maternity personnel in obstetrical emergency care and neonatal resuscitation. 4. Providing four quality prenatal visits. 5. Providing quality cesarean deliveries. 6. Supporting the Mozambican Government's campaign against bribery.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

Health provider responsiveness to social accountability initiatives in low- and middle-income countries: a realist review - Lodenstein, Elsbet; Dieleman, Marjolein; Gerretsen, Barend; Broerse, Jacqueline E W (Health Policy and Planning, 2017)
Social accountability in the health sector has been promoted as a strategy to improve the quality and performance of health providers in low- and middle-income countries. Whether improvements occur, however, depends on the willingness and ability of health providers to respond to societal pressure for better care. This article uses a realist approach to review cases of collective citizen action and advocacy with the aim to identify key mechanisms of provider responsiveness. Purposeful searches for cases were combined with a systematic search in four databases. To be included in the review, the initiatives needed to describe at least one outcome at the level of frontline service provision. Some 37 social accountability initiatives in 15 countries met these criteria. Using a realist approach, retroductive analysis and triangulation of methods and sources were performed to construct Context–Mechanism–Outcome configurations that explain potential pathways to provider responsiveness. The findings suggest that health provider receptivity to citizens’ demands for better health care is mediated by health providers’ perceptions of the legitimacy of citizen groups and by the extent to which citizen groups provide personal and professional support to health providers. Some citizen groups activated political or formal bureaucratic accountability channels but the effect on provider responsiveness of such strategies was more mixed. Favourable contexts for health provider responsiveness comprise socio-political contexts in which providers self-identify as activists, health system contexts in which health providers depend on citizens’ expertise and capacities, and health system contexts where providers have the self-perceived ability to change the system in which they operate. Rather than providing recipes for successful social accountability initiatives, the synthesis proposes a programme theory that can support reflections on the theories of change underpinning social accountability initiatives and interventions to improve the quality of primary health care in different settings.
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde

Maternity care system in Maputo, Mozambique: Plans and practice? - Long, Qian; Madede, Tavares; Parkkali, Saara; Chavane, Leonardo; Sundby, Johanne; Hemminki, Elina (Cogent Medicine, 2017)
Mixed methods were used with various data sources to describe organisation and delivery of maternity care in Maputo city, Mozambique in early 2010s and to compare the plans with the service provision in practice. In the public health sector, maternity care was organised to be area based and hierarchical with a planned referral system. The provision of basic and emergency maternity care was publicly funded, largely dependent of donor funds, and free of charge for users. Even though Maputo City was better resourced than the rest of the country, there was a large lack of health professionals. Women’s choices and self-referrals, even to higher levels of care, were common, which broke the plans of areas responsibility, gate keeping and care by medical needs. Private services for maternity care had emerged for those who were able to pay, leading to dual practices of health professionals and shortage of care providers in the public system at odd hours. Information of maternity care was aggregate and poorly stored. The gap between “planned” services delivery and “practice” in a real-life requires overall health system strengthening to improve efficiency and effectiveness of health services delivery.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Desafio da articulação entre os cidadãos e os Comités de Qualidade e Humanização dos Cuidados de Saúde como órgãos de representação da comunidade - Dias, José (Centro de Aprendizagem e Capacitação da Sociedade Civil, 2017)
O Ministério da Saúde reconhece os Comités de Qualidade e Humanização dos Cuidados de Saúde nas Unidades Sanitárias como a principal forma de diálogo e ligação entre os serviços de saúde e as comunidades. Os Termos de Referência revistos, afirmam que o Comité de Qualidade e Humanização das Unidades Sanitárias constitui uma equipa de assessoria e coordenação ao processo de implementação da actividades de qualidade e humanização no âmbito da Unidade Sanitária. Destina-se a empreender uma política institucional de resgate de valores humanitários e de garantia de qualidade nos serviços de saúde, em benefício dos utentes e trabalhadores através da gestão participativa. Contudo, o sector de saúde dispõe também da Carta dos Direitos e Deveres do Doente, como instrumento que, no nosso entendimento, define o padrão da prestação de serviços, de comportamento, e concede espaço ao cidadão, individual ou colectivamente, para a exigência directa de serviços de saúde de qualidade. A este último propósito, por exemplo, cabe ressaltar que no quadro do Direito 16 (Direito a apresentar sugestões, queixas e reclamações) é estabelecido que através dos canais disponibilizados pelas Autoridades Sanitárias, os doentes têm direito a apresentar, individual ou colectivamente, petições, sugestões, reclamações ou queixas sobre a organização e o funcionamento dos serviços de saúde; e de ter as suas queixas atendidas prontamente e de maneira equitativa (MISAU, 2011). O que se apreende do exposto é que enquanto os Comités de Qualidade e Humanização funcionam numa lógica essencialmente de Democracia Representativa, a Carta dos Direitos e Deveres do Doente se insere numa abordagem de Democracia Participativa, buscando promover uma cidadania activa do doente/cidadão na sua interacção directa com as unidades sanitárias. O nosso artigo problematiza e discute as dinâmicas de representação e de participação activa do cidadão no processo da prestação de serviços de saúde. A nossa base de discussão é fundamentada em evidências de 15 distritos de actuação do Centro de Aprendizagem e Capacitação da Sociedade Civil (CESC), onde funcionam os Comités de Qualidade e Humanização, por um lado, e se implementa a abordagem de Responsabilização Social, usando ferramentas tais como Cartão de Pontuação Comunitária, por outro.
Keywords: G - Mozambique / Moçambique; Health PEA; L - portuguese / português; access to services / acesso a serviços; citizenship & participation / cidadania e participação; health / saúde

Estratégia Científica 2016-2015 - Instituto Nacional da Saúde - Moçambique (Instituto Nacional da Saúde - Moçambique, 2017)
A presente Estratégia Científica do Instituto Nacional de Saúde (INS) para 2016-2025 está alinhada com o Programa Quinquenal do Governo (2015-2019) e com o Plano Estratégico do Sector Saúde (PESS 2014-2019). No contexto global, a elaboração da presente Estratégia teve em conta os Objectivos de Desenvolvimento Sustentável (ODS), o Regulamento Sanitário Internacional (RSI) e a Agenda Global de Segurança Sanitária (GHSA). As principais diferenças entre a presente e anterior estratégia do INS são: 1) um horizonte temporal incrementado, sendo de 10 anos ao contrário de 5 anos na estratégia anterior; 2) uma ampliação das áreas programáticas estratégicas; 3) a inclusão de um robusto eixo estratégico de fortalecimento na área de gestão institucional. A Estratégia Científica do INS 2016-2025 está organizada em Programas e em Eixos Estratégicos. Os oito Programas desta Estratégia Científica reflectem as áreas temáticas consideradas como prioritárias. Estes Programas são: 1) Saúde e Ambiente, incluindo Saúde do Trabalhador; 2) Saúde Mental, Trauma e Violência; 3) Saúde da Mulher e da Criança; 4) Adolescente, Idoso e Outras Populações Vulneráveis; 5) Determinantes de Doenças Crónicas; 6) Doenças Transmitidas por Vectores, Negligenciadas e Zoonóticas; 7) Doenças Endémicas de Grande Impacto Sanitário; 8) Sistema de Saúde. Os cinco Eixos Estratégicos representam as funções essenciais de saúde pública. Este Eixos Estratégicos são: 1) Observatório Nacional de Saúde e Vigilância Epidemiológica; 2) Rede de Laboratórios de Referência em Saúde; 3) Pesquisa, Desenvolvimento Tecnológico e Inovação; 4) Ensino, Informação e Comunicação em Saúde; 5) Gestão e Desenvolvimento Institucional. Cada Programa e Eixo Estratégico tem um ou mais Objetivos Estratégicos e seus respectivos indicadores de impacto, cada um dos quais descreve a situação ideal que se pretende atingir a médio e longo prazo. Cada Objectivo Estratégico deve ser atingido mediante a execução de uma ou mais Acções cujo enunciado reflete num conjunto de Projectos/Actividades afins. Os Projectos são actividades com objectivos e temporalidade definidas, enquanto se denominam Actividades aquelas outras que são de carácter continuado, geralmente de gestão. Finalmente, cada Projecto/Actividade tem Produtos, Indicadores e Metas temporais e/ou quantitativas definidas. Os Projectos/Actividades temáticos encontram-se descritos em cada um dos oito programas, enquanto os Projectos/Actividades estruturantes encontram-se descritos em cada um dos cinco eixos estratégicos. A presente Estratégia Científica compreende 17 Objectivos Estratégicos, 19 Acções e 102 Projectos / Actividades.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - health services / serviços de saúde

Perspectives on the coordination of multisectoral nutrition in Mozambique and an emerging framework - Michaud-Létourneau, Isabelle; Pelletier, David Louis (Food Policy, 2017)
Multisectoral approaches represent a prominent ideological consensus, inﬂuenced by historical roots and the current political, ﬁnancial and institutional landscape, to address the multi-faceted and complex causes of most nutrition, public health and food problems. However, the implementation of multisectoral approaches presents tremendous challenges; one of the most often cited problems, in the literature and by practitioners, is coordination. This study investigates the perspectives of key national leaders on a range of issues regarding the coordination of a Multisectoral Action Plan for the Reduction of Chronic Undernutrition (PAMRDC) in Mozambique. Within this policy group, the principal researcher played the role of a researcher-participant for 14 months, and used Q methodology with a total of 21 key national leaders who had been actively engaged in coordination groups at the central level. Participants sorted 54 subjective statements on a range of issues that were present in the current national discourse. The results revealed four distinct perspectives. The Implementation perspective (n = 12) prioritized concrete actions to advance the operationalization of the plan, based on a guidance-based approach from the central level to the lower administrative levels. The Advocacy perspective (n = 3) emphasized advocacy to increase politicians’ awareness of the problem and of potential solutions to enhance political commitment. The Structuralist perspective (n = 3) was concerned with the development of structures and mechanisms to facilitate coordination, funding and improving communication between the government and donors. The People-centered perspective (n = 3) focused on the importance of mobilizing individuals to compensate for the sub-optimal structures and processes for coordination. Areas of convergence across the perspectives included: low capacity and skills that limit the work; the agency in charge of coordination (SETSAN) should exercise an increased leadership to facilitate the multisectoral work; and SETSAN should advocate to mobilize politicians and donors for resources. Areas of divergence related to the type of guidance from national to sub-national levels (prescriptive or not) and the functions to be carried out by SETSAN. This study highlights lack of clarity on the meaning of coordination and on the functions of the multisectoral coordination body that appear to arise for two reasons: the lack of an explicit and shared framework for the policy process and the complex nature of coordination itself. These results are examined through the lenses of several related literatures, including governance, public policy and political economy of nutrition, leading to a three-dimensional conceptual framework for coordination that distinguishes the coordination space, forms, and instruments. Global guidance, such as provided through the SUN movement, could support countries in overcoming their coordination challenges by facilitating an analysis of their decision-making processes in order to choose the functions for the coordination body based on a shared understanding of countries’ needs, context and opportunities. This paper moves the ﬁeld beyond a broad consideration of horizontal and vertical coordination within multisectoral initiatives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Austerity and the “sector-wide approach” to health: The Mozambique experience - Pfeiffer, James; Gimbel, Sarah; Chilundo, Baltazar; Gloyd, Stephen; Chapman, Rachel; Sherr, Kenneth (Social Science & Medicine, 2017)
Fiscal austerity policies imposed by the IMF have reduced investments in social services, leaving postindependence nations like Mozambique struggling to recover from civil war and high disease burden. By 2000, a sector-wide approach (SWAp) was promoted to maximize aid effectiveness. ‘Like-minded’ bilateral donors, from Europe and Canada, promoted a uniﬁed approach to health sector support focusing on joint planning, common basket funding, and streamlined monitoring and evaluation to improve sector coordination, amplify country ownership, and build sustainable health systems. Notable donors e including US government and the Global Fund e did not participate in the SWAp, and increased vertical funding weakened the SWAp in favor of non-governmental organizations (NGOs). In spite of some success in harmonizing aid to the health sector, the SWAp experience in Mozambique demonstrates how continued austerity regimes that severely constrain public spending will continue to undermine health system strengthening in Africa, even in the midst of high levels of foreign aid with the ostensible purpose of strengthening those systems. The SWAp story provides a poignant illustration of how continued austerity will impede progress toward Sustainable Development Goal 3 (SDG 3); “Achieve universal health coverage, including ﬁnancial risk protection, access to quality essential health-care services and access to safe, effective, quality and affordable essential medicines and vaccines for all”. However, the SWAp continues to offer an alternative model to health system support that can provide a foundation for resistance to renewed austerity measures.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; fiscal policy / política fiscal; health / saúde

População da Ilha de Moçambique queixa-se de cobranças ilícitas na maternidade - Televisão de Moçambique TVM (Televisão de Moçambique TVM, 2016)
Primeira sessão do dia aberto ao cidadão, uma iniciativa do conselho municipal da ilha de Moçambique para escutar as questões que atinjem os cerca de 50mil habitantes da primeira capital de Moçambique. As reuniões são realizadas nas comunidades para que de forma franca e aberta os munícipes possam apresentar os seus problemas
Keywords: G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Place, Time and Experience: Barriers to Universalization Of Institutional Child Delivery in Rural Mozambique - Agadjanian, Victor; Yao, Jing; Hayford, Sarah R (International perspectives on sexual and reproductive health, 2016)
CONTEXT: Although institutional coverage of childbirth is increasing in the developing world, a substantial minority of births in rural Mozambique still occur outside of health facilities. Identifying the remaining barriers to safe professional delivery services can aid in achieving universal coverage. METHODS: Survey data collected in 2009 from 1,373 women in Gaza, Mozambique, were used in combination with spatial, meteorological and health facility data to examine patterns in place of delivery. Geographic information system-based visualization and mapping and exploratory spatial data analysis were used to outline the spatial distribution of home deliveries. Multilevel logistic regression models were constructed to identify associations between individual, spatial and other characteristics and whether women's most recent delivery took place at home. RESULTS: Spatial analysis revealed high- and low-prevalence clusters of home births. In multivariate analyses, women with a higher number of clinics within 10 kilometers of their home had a reduced likelihood of home delivery, but those living closer to urban centers had an increased likelihood. Giving birth during the rainy, high agricultural season was positively associated with home delivery, while household wealth was negatively associated with home birth. No associations were evident for measures of exposure to and experience with health institutions. CONCLUSIONS: The results suggest the need for a comprehensive approach to expansion of professional delivery services. Such an approach should complement measures facilitating physical access to health institutions for residents of harder-to-reach areas with community-based interventions aimed at improving rural women's living conditions and opportunities, while also taking into account seasonal and other variables.
Keywords: G - Mozambique / Moçambique; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Effects of food price shocks on child malnutrition: The Mozambican experience 2008/2009 - Arndt, Channing; Hussain, M. Azhar; Salvucci, Vincenzo; Østerdal, Lars Peter (Elsevier, 2016)
A propitiously timed household survey carried out in Mozambique over the period 2008/ 2009 permits us to study the relationship between shifts in food prices and child nutrition status in a low income setting. We focus on weight-for-height and weight-for-age in different survey quarters characterized by very different food price inflation rates. Using propensity score matching techniques, we find that these nutrition measures, which are sensitive in the short run, improve significantly in the fourth quarter of the survey, when the inflation rate for basic food products is low, compared to the first semester or three quarters, when food price inflation was generally high. The prevalence of underweight, in particular, falls by about 40 percent. We conclude that the best available evidence points to food penury, driven by the food and fuel price crisis combined with a short agricultural production year, as substantially increasing malnutrition amongst under-five children in Mozambique.
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde; ⛔ No DOI found

Barriers and facilitators to health care seeking behaviours in pregnancy in rural communities of southern Mozambique - Munguambe, Khátia; Boene, Helena; Vidler, Marianne; Bique, Cassimo; Sawchuck, Diane; Firoz, Tabassum; Makanga, Prestige Tatenda; Qureshi, Rahat; Macete, Eusébio; Menéndez, Clara; von Dadelszen, Peter; Sevene, Esperança (Reproductive Health, 2016)
Background: In countries, such as Mozambique, where maternal mortality remains high, the greatest contribution of mortality comes from the poor and vulnerable communities, who frequently reside in remote and rural areas with limited access to health care services. This study aimed to understand women’s health care seeking practices during pregnancy, taking into account the underlying social, cultural and structural barriers to accessing timely appropriate care in Maputo and Gaza Provinces, southern Mozambique. Methods: This ethnographic study collected data through in-depth interviews and focus group discussions with women of reproductive age, including pregnant women, as well as household-level decision makers (partners, mothers and mothers-in-law), traditional healers, matrons, and primary health care providers. Data was analysed thematically using NVivo 10. Results: Antenatal care was sought at the heath facility for the purpose of opening the antenatal record. Women without antenatal cards feared mistreatment during labour. Antenatal care was also sought to resolve discomforts, such as headaches, flu-like symptoms, body pain and backache. However, partners and husbands considered lower abdominal pain as the only symptom requiring care and discouraged women from revealing their pregnancy early in gestation. Health care providers for pregnant women often included those at the health facility, matrons, elders, traditional birth attendants, and community health workers. Although seeking care from traditional healers was discouraged during the antenatal period, they did provide services during pregnancy and after delivery. Besides household-level decision-makers, matrons, community health workers, and neighbours were key actors in the referral of pregnant women. The decision-making process may be delayed and particularly complex if an emergency occurs in their absence. Limited access to transport and money makes the decision-making process to seek care at the health facility even more complex.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Gaza; GP - Maputo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

For an efficient, decentralised, transparent and inclusive health system - N'weti (N'weti, 2016)
Recommendations: 1. On planning and budgeting, greater coordination is recommended between planning (setting priorities) and budgeting (financial apportionment). Transformation of all District Health Services, Women and Social Action (SDSMAS) into Management Beneficiary Units (MBU) is necessary. 2. Stakeholders should bet more on application of national public financial management systems (PFM). The use of parallel financial systems instead of enabling the National Health System (NHS) to be more e cient hinders the enhancement of the sector’s PFM systems. 3. With regard to budgeting, zero-based budgeting implementation is recommended, replacing the incremental budgeting system. Zero-based budgeting is more realistic in so far as the health sector operation costs are concerned. 4. On the decentralisation and citizen participation component, the establishment of a national plan for decentralisation in the health sector is recommended. This plan would allow systematise local citizen participation mechanisms in the health system management and monitoring. 5. On revenue collection, the sector authorities need to explore areas of potential revenue already identified in Intellica’s 2013 research report, such as drug prescription, outpatient, medical certificate rates; and comply with the Decree 11/2007 of 30 May, which regulates tobacco consumption and sale, which has great potential to generate revenue for the health sector at the district level, by means of fines on the lawbreakers. 6. A Policy Brief drawn from the Public Expenditure Tracking Survey (PETS) in the Health Sector in Angoche, Bilene, Magude and Xai-Xai districts, and Chamanculo and José Macamo General Hospitals On expenditure performance, more and better coordination among stakeholders at district levels and Health Centres is recommended in order to avoid expenditure implementation costs in a fragmented and uncoordinated manner. 7. On procurement, accuracy improvement is recommended for the current legal framework implementation. This is to ensure that Procurement Management Units (PMUs) are practical; they can perform their tasks with independence, impartiality and professionalism. The direct award should always be treated as provided for in the law (an exception) and not deemed as the rule like what we have noticed occur in the researched cases. The document disorderliness of the Procurement Management Units portfolios can be solved with portfolio digitisation, ensuring more and better file and document handling, more control and additional transparency. 8. On transparency, recommendation to the Ministry of Health (MoH) is on the establishment of mechanisms which may ensure that sector o cials, who handle equal duties, should have the same understanding about procedures, not only in the health sector, but also in liaison with other sectors and society in general. When applying the Right to Information Act, Civil Society Organizations (CSOs) should now carry out awareness raising sessions and dialogue with sector o cials in order to reach mutual understanding on the added value that represents transparent public service management, with accountability and civil society influence, through monitoring and evaluation.
Keywords: *indexed; *non-public; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; GD - Bilene; GD - Magude; GD - Xai-Xai; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; budget / orçamento; decentralization / descentralização; health / saúde

Network advocacy and the emergence of global attention to newborn survival - Shiffman, Jeremy (Health Policy and Planning, 2016)
Globally 2.9 million babies die each year before reaching 28 days of life. Over the past quarter century, neonatal mortality has declined at a slower pace than post-neonatal under-five mortality: in consequence newborns now comprise 44% of all deaths to children under five years. Despite high numbers of newborn deaths, global organizations and national governments paid little attention to the issue until 2000, and resources, while growing since then, remain inadequate. This study examines the factors behind these patterns of policy attention: the delayed emergence of attention, its sudden appearance in 2000, its growth thereafter, but the dearth of resources to date. Drawing on a framework on global health networks grounded in collective action theory, the study finds that a newborn survival network helped to shift perceptions about the problem’s severity and tractability, contributing to the rise of global attention. Its efforts were facilitated by pressure on governments to achieve the child survival Millennium Development Goal and by growing awareness that the neonatal period constituted a growing percentage of under-five mortality, a fact the network publicized. The network’s relatively recent emergence, its predominantly technical rather than political composition and strategies, and its inability to date to find a framing of the issue that has convinced national political leaders of the issue’s urgency, in part explain the insufficiency of resources. However, since 2010 a number of non-health oriented inter-governmental organizations have begun to pay attention to the issue, and several countries with high neonatal mortality have created national plans, developments which augur well for the future. The study points to two broader implications concerning how neglected global health issues come to attract attention: priority emerges from a confluence of factors, rather than any single cause; and growth in priority may depend on the creation of a broader political coalition that extends beyond the largely technically oriented actors who may first press for attention to a problem.
Keywords: L - english / inglês; collaboration / colaboração; health - maternal and child / saúde - materno-infantil; health / saúde

A framework on the emergence and effectiveness of global health networks - Shiffman, Jeremy; Quissell, Kathryn; Schmitz, Hans Peter; Pelletier, David L; Smith, Stephanie L; Berlan, David; Gneiting, Uwe; Van Slyke, David; Mergel, Ines; Rodriguez, Mariela; Walt, Gill (Health policy and planning, 2016)
Since 1990 mortality and morbidity decline has been more extensive for some conditions prevalent in low- and middle-income countries than for others. One reason may be differences in the effectiveness of global health networks, which have proliferated in recent years. Some may be more capable than others in attracting attention to a condition, in generating funding, in developing interventions and in convincing national governments to adopt policies. This article introduces a supplement on the emergence and effectiveness of global health networks. The supplement examines networks concerned with six global health problems: tuberculosis (TB), pneumonia, tobacco use, alcohol harm, maternal mortality and newborn deaths. This article presents a conceptual framework delineating factors that may shape why networks crystallize more easily surrounding some issues than others, and once formed, why some are better able than others to shape policy and public health outcomes. All supplement papers draw on this framework. The framework consists of 10 factors in three categories: (1) features of the networks and actors that comprise them, including leadership, governance arrangements, network composition and framing strategies; (2) conditions in the global policy environment, including potential allies and opponents, funding availability and global expectations concerning which issues should be prioritized; (3) and characteristics of the issue, including severity, tractability and affected groups. The article also explains the design of the project, which is grounded in comparison of networks surrounding three matched issues: TB and pneumonia, tobacco use and alcohol harm, and maternal and newborn survival. Despite similar burden and issue characteristics, there has been considerably greater policy traction for the first in each pair. The supplement articles aim to explain the role of networks in shaping these differences, and collectively represent the first comparative effort to understand the emergence and effectiveness of global health networks.
Edition: 2015/08/29 Publisher: Oxford University Press
Keywords: L - english / inglês; collaboration / colaboração; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Agenda setting for maternal survival: the power of global health networks and norms - Smith, Stephanie L; Rodriguez, Mariela A (Health Policy and Planning, 2016)
Nearly 300 000 women—almost all poor women in low-income countries—died from pregnancy-related complications in 2010. This represents a decline since the 1980s, when an estimated half million women died each year, but is still far higher than the aims set in the United Nations Millennium Development Goals (MDGs) at the turn of the century. The 1970s, 1980s and 1990s witnessed a shift from near complete neglect of the issue to emergence of a network of individuals and organizations with a shared concern for reducing maternal deaths and growth in the number of organizations and governments with maternal health strategies and programmes. Maternal health experienced a marked change in agenda status in the 2000s, attracting significantly higher level attention (e.g. from world leaders) and greater resource commitments (e.g. as one issue addressed by US$40 billion in pledges to the 2010 Global Strategy for Women’s and Children’s Health ) than ever before. Several differences between network and actor features, issue characteristics and the policy environment pre- and post-2000 help to explain the change in agenda status for global maternal mortality reduction. Significantly, a strong poverty reduction norm emerged at the turn of the century; represented by the United Nations MDGs framework, the norm set unusually strong expectations for international development actors to advance included issues. As the norm grew, it drew policy attention to the maternal health goal (MDG 5). Seeking to advance the goals agenda, world leaders launched initiatives addressing maternal and child health. New network governance and framing strategies that closely linked maternal, newborn and child health shaped the initiatives. Diverse network composition—expanding beyond a relatively narrowly focused and technically oriented group to encompass allies and leaders that brought additional resources to bear on the problem—was crucial to maternal health’s rise on the agenda in the 2000s.
Keywords: L - english / inglês; collaboration / colaboração; health - maternal and child / saúde - materno-infantil; health / saúde

Mapping the use of research to support strategies tackling maternal and child health inequities: evidence from six countries in Africa and Latin America - Vargas, Emily; Becerril-Montekio, Victor; Gonzalez-Block, Miguel Ángel; Akweongo, Patricia; Hazel, Cynthia N. A.; Cuembelo, Maria de Fatima; Limbani, Felix; Bernardo, Wanderley; Muñoz, Fernando (Health Research Policy and Systems, 2016)
Background: Striving to foster collaboration among countries suffering from maternal and child health (MCH) inequities, the MASCOT project mapped and analyzed the use of research in strategies tackling them in 11 low- and middle-income countries. This article aims to present the way in which research influenced MCH policies and programs in six of these countries – three in Africa and three in Latin America. Methods: Qualitative research using a thematic synthesis narrative process was used to identify and describe who is producing what kind of research, how research is funded, how inequities are approached by research and policies, the countries’ research capacities, and the type of evidence base that MCH policies and programs use. Four tools were designed for these purposes: an online survey for researchers, a semi-structured interview with decision makers, and two content analysis guides: one for policy and programs documents and one for scientific articles. Results: Three modalities of research utilization were observed in the strategies tackling MCH inequities in the six included countries – instrumental, conceptual and symbolic. Instrumental utilization directly relates the formulation and contents of the strategies with research results, and is the least used within the analyzed policies and programs. Even though research is considered as an important input to support decision making and most of the analyzed countries count five or six relevant MCH research initiatives, in most cases, the actual impact of research is not clearly identifiable. Conclusions: While MCH research is increasing in low- and middle-income countries, the impact of its outcomes on policy formulation is low. We did not identify a direct relationship between the nature of the financial support organizations and the kind of evidence utilization within the policy process. There is still a visible gap between researchers and policymakers regarding their different intentions to link evidence and decision making processes.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Direct observation of respectful maternity care in five countries: a cross-sectional study of health facilities in East and Southern Africa - Rosen, Heather E.; Lynam, Pamela F.; Carr, Catherine; Reis, Veronica; Ricca, Jim; Bazant, Eva S.; Bartlett, Linda A.; on behalf of the Quality of Maternal and Newborn Care Study Group of the Maternal and Child Health Integrated Program (BMC Pregnancy and Childbirth, 2015)
Poor quality of care at health facilities is a barrier to pregnant women and their families accessing skilled care. Increasing evidence from low resource countries suggests care women receive during labor and childbirth is sometimes rude, disrespectful, abusive, and not responsive to their needs. However, little is known about how frequently women experience these behaviors. This study is one of the first to report prevalence of respectful maternity care and disrespectful and abusive behavior at facilities in multiple low resource countries.
Keywords: G - Mozambique / Moçambique; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Mulheres denunciam corrupção nas maternidades de Nampula - Voa Português (Voa Português, 2015)
Parteiras exigem entre 500 e 2.000 meticais para realizar partos. Cobranças ilícitas nas maternidades das unidades sanitárias em Nampula, Moçambique, estão a comprometer a qualidade do atendimento materno-infantil e a “forçar” as grávidas a optarem por ter filhos na comunidade. Algumas mulheres ouvidas pela VOA no Hospital Central de Nampula denunciaram o mau atendimento nas unidades sanitárias. Acusam ainda profissionais de cobrarem entre 500 e 2.000 meticais para realizar um parto.
Keywords: G - Mozambique / Moçambique; GP - Nampula; L - portuguese / português; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Challenges and opportunities for implementing evidence-based antenatal care in Mozambique: a qualitative study - Biza, Adriano; Jille-Traas, Ingeborg; Colomar, Mercedes; Belizan, Maria; Requejo Harris, Jennifer; Crahay, Beatrice; Merialdi, Mario; Nguyen, My Huong; Althabe, Fernando; Aleman, Alicia; Bergel, Eduardo; Carbonell, Alicia; et al. (BMC Pregnancy and Childbirth, 2015)
Background: Maternal mortality remains a daunting problem in Mozambique and many other low-resource countries. High quality antenatal care (ANC) services can improve maternal and newborn health outcomes and increase the likelihood that women will seek skilled delivery care. This study explores the factors influencing provider uptake of the recommended package of ANC interventions in Mozambique. Methods: This study used qualitative research methods including key informant interviews with stakeholders from the health sector and a total of five focus group discussions with women with experience with ANC or women from the community. Study participants were selected from three health centers located in Maputo city, Tete, and Cabo Delgado provinces in Mozambique. Staff responsible for the medicines/supply chain at national, provincial and district level were interviewed. A check list was implemented to confirm the availability of the supplies required for ANC. Deductive content analysis was conducted. Results: Three main groups of factors were identified that hinder the implementation of the ANC package in the study setting: a) system or organizational: include chronic supply chain deficiencies, failures in the continuing education system, lack of regular audits and supervision, absence of an efficient patient record system and poor environmental conditions at the health center; b) health care provider factors: such as limited awareness of current clinical guidelines and a resistant attitude to adopting new recommendations; and c) Users: challenges with accessing ANC, poor recognition amongst women about the purpose and importance of the specific interventions provided through ANC, and widespread perception of an unfriendly environment at the health center. Conclusions: The ANC package in Mozambique is not being fully implemented in the three study facilities, and a major barrier is poor functioning of the supply chain system. Recommendations for improving the implementation of antenatal interventions include ensuring clinical protocols based on the ANC model. Increasing the community understanding of the importance of ANC would improve demand for high quality ANC services. The supply chain functioning could be strengthened through the introduction of a kit system with all the necessary supplies for ANC and a simple monitoring system to track the stock levels is recommended.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Cabo Delgado; GP - Tete; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

N’weti’s Community Scorecard Experience in Nampula: a Case Study - Franco, Erika Lopez; Dumangane, Sansão (Institute of Development Studies and N'weti, 2015)
This case study was commissioned by N’weti Comunicação para a Saúde to explore the changes emerging from the implementation of an adapted version of the Community Scorecard (CSC) tool in 11 health facilities catchment areas in Nampula. This case study discusses how N’weti has adapted the Community Scorecard (CSC) tool to better improve the quality of the participation and prospects of accountability for citizens. The case study presents evidence that the adapted CSC tool has resulted in an increased awareness of rights, an improved relationship with the service providers, a revitalisation of the health unit Co-management Committees, citizens feeling that their voice is being heard, and N’weti is recognised by people and authorities as catalyser and legitimate mediator of this voice. However, challenges also surfaced which N’weti must reflect and learn from. The first relates to the meaningful control from regular citizens (rather than NGO staff members) of the institutionalisation, follow-up of commitments and advocacy actions derived from the implementation of a CSC process. Other challenges refer to social exclusion, the lack of a deeper understanding of power dynamics, and the fact that ignoring previous histories of citizen engagement and other contextual factors can be misleading as not all change can be directly attributed to the implementation of the CSC.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Meconta; GD - Moma; GD - Rapale; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Child Marriage and Adolescent Pregnancy in Mozambique: Policy Brief - Hodges, Anthony (UNFPA, Meninas e Não Noivas, UNICEF, 2015)
Child marriage is one of Mozambique’s most serious but largely ignored development challenges – requiring far greater attention from policy makers Child marriage rates are still very high despite a long-term decline, especially in marriage before the age of 15. Economic pressures and the incentive of bride price appear to be powerful factors driving parents to marry off their daughters at a young age. The high rates of child marriage cannot be allowed to continue without a vigorous response from the government, civil society and development partners.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

The global epidemic of abuse and disrespect during childbirth: History, evidence, interventions, and FIGO's mother−baby friendly birthing facilities initiative - Miller, Suellen; Lalonde, Andre (International Journal of Gynecology & Obstetrics, 2015)
Abstract Recent evidence indicates that disrespectful/abusive/coercive service delivery by skilled providers in facilities, which results in actual or perceived poor quality of care, is directly and indirectly associated with adverse maternal and newborn outcomes. The present article reviews the evidence for disrespectful/abusive care during childbirth in facilities (DACF), describes examples of DACF, discusses organizations active in a rights-based respectful maternity care movement, and enumerates some strategies and interventions that have been identified to decrease DACF. It concludes with a discussion of one strategy, which has been recently implemented by FIGO with global partners?the International Pediatrics Association, International Confederation of Midwives, the White Ribbon Alliance, and WHO. This strategy, the Mother and Baby Friendly Birth Facility (MBFBF) Initiative, is a criterion-based audit process based on human rights' doctrines, and modeled on WHO/UNICEF's Baby Friendly Facility Initiative.
Publisher: John Wiley & Sons, Ltd
Keywords: L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Socio-economic and Community Health Baseline - Anadarko Mozambique (ExxonMobil, 2014)
This chapter outlines the socio-economic and health baseline of areas (both onshore and offshore) potentially affected by the Project. The chapter is structured into a number of sections, as follows: • Sections 9.2 and 9.3 provide a summary of the baseline and sources of information used to compile the baseline, respectively. • Section 9.4 defines the Project Area of Influence, providing both an overview of the geographic characteristics as well as the respective administrative divisions and governance structures. • Sections 9.5 to 9.7 provide an overview of Cabo Delgado Province (an important part of the Area of Indirect Influence) and aims to set the broader social, health and economic context in which the Project will be located. • Sections 9.8 to 9.14 provide a description of the social, health and economic characteristics of the Area of Direct Influence, which includes Palma District and the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.15 provides a description of the cultural and religious profile of the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.16 provides an overview of perceptions and expectations about the Project. • Section 9.17 provides an understanding of the shipping movements and types of vessels used within the Study Area. • Section 9.18 details the archaeology and cultural heritage baseline of the Afungi Project Site, based on both primary and secondary data.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; health / saúde; poverty / pobreza

Disrespect and Abuse During Childbirth in Tanzania: Are Women Living With HIV More Vulnerable? - Sando, David; Kendall, Tamil; Lyatuu, Goodluck; Ratcliffe, Hannah; McDonald, Kathleen; Mwanyika-Sando, Mary; Emil, Faida; Chalamilla, Guerino; Langer, Ana (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2014)
Introduction: HIV-related stigma and discrimination and disrespect and abuse during childbirth are barriers to use of essential maternal and HIV health services. Greater understanding of the relationship between HIV status and disrespect and abuse during childbirth is required to design interventions to promote women's rights and to increase uptake of and retention in health services; however, few comparative studies of women living with HIV (WLWH) and HIV-negative women exist. Methods: Mixed methods included interviews with postpartum women (n = 2000), direct observation during childbirth (n = 208), structured questionnaires (n = 50), and in-depth interviews (n = 18) with health care providers. Bivariate and multivariate regressions analyzed associations between HIV status and disrespect and abuse, whereas questionnaires and in-depth interviews provided insight into how provider attitudes and workplace culture influence practice. Results: Of the WLWH and HIV-negative women, 12.2% and 15.0% reported experiencing disrespect and abuse during childbirth (P = 0.37), respectively. In adjusted analyses, no significant differences between WLWH and HIV-negative women's experiences of different types of disrespect and abuse were identified, with the exception of WLWH having greater odds of reporting non-consented care (P = 0.03). None of the WLWH reported violations of HIV confidentiality or attributed disrespect and abuse to their HIV status. Provider interviews indicated that training and supervision focused on prevention of vertical HIV transmission had contributed to changing the institutional culture and reducing HIV-related violations. Conclusions: In general, WLWH were not more likely to report disrespect and abuse during childbirth than HIV-negative women. However, the high overall prevalence of disrespect and abuse measured indicates a serious problem. Similar institutional priority as has been given to training and supervision to reduce HIV-related discrimination during childbirth should be focused on ensuring respectful maternity care for all women.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Joint Assessment of the Mozambican Health Sector Strategic Plan (PESS, 2014-2019) - JANS - Joint Assessment of National Strategies (International Health Partnership, 2013)
Since independence in 1975, development in Mozambique has been guided by a sequence of Five Year Plans, (Planos Quinquenais de Desenvolvimento). In 2002 the Government of Mozambique (GOM) initiated a series of reforms in all development sectors, aiming to start a process of decentralisation and bringing management closer to the lower levels of state organisation (Provinces and Districts). For the Municipalities, a devolution model was chosen that is currently in the process of being rolled out to all municipalities in the country. It is within this context that the health sector initiated its Five Year Strategic Plans (Plano Estrategico do Sector da Saúde - PESS) in 2000 with the aim to gradually improve the health status of the people. The current PESS is the third of its kind (PESS III), representing a continuation of this good management practice in the country, aiming to improve access and quality of current services (Pilar 1), while at the same time continuing a series of Reforms within the health sector that aim to improve effectiveness and efficiency in overall service provision at all levels (Pilar 2). The health sector distinguishes four levels of service provision, going from Health Posts and Health Centres at the level of villages and sub-districts to District Hospitals to Provincial Hospitals and finally to the Central / Specialised Hospitals at the top of the health pyramid.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; decentralization / descentralização; health / saúde

Measuring Coverage in MNCH: Testing the Validity of Women's Self-Report of Key Maternal and Newborn Health Interventions during the Peripartum Period in Mozambique - Stanton, Cynthia K.; Rawlins, Barbara; Drake, Mary; dos Anjos, Matias; Cantor, David; Chongo, Lidia; Chavane, Leonardo; da Luz Vaz, Maria; Ricca, Jim (PLoS ONE, 2013)
Background: As low-income countries strive to meet targets for Millennium Development Goals 4 and 5, there is growing need to track coverage and quality of high-impact peripartum interventions. At present, nationally representative household surveys conducted in low-income settings primarily measure contact with the health system, shedding little light on content or quality of care. The objective of this study is to validate the ability of women in Mozambique to report on facility-based care they and their newborns received during labor and one hour postpartum. Methods and Findings: The study involved household interviews with women in Mozambique whose births were observed eight to ten months previously as part of a survey of the quality of maternal and newborn care at government health facilities. Of 487 women whose births were observed and who agreed to a follow-up interview, 304 were interviewed (62.4%). The validity of 34 indicators was tested using two measures: area under receiver operator characteristic curve (AUC) and inflation factor (IF); 27 indicators had sufficient numbers for robust analysis, of which four met acceptability criteria for both (AUC .0.6 and 0.75,IF,1.25). Two of these indicators are considered high demand and are recommended for incorporation into international survey programs: presence of a support person during labor/delivery and placement of the newborn skin to skin against the mother. Nine indicators met acceptability criteria for one of the validity measures. All 13 indicators are recommended for use in in-depth maternal/newborn health surveys. Conclusions: Women are able to report on some aspects of peripartum care. Larger studies may be able to validate some indicators that this study could not assess due to the sample size. Future qualitative research may assist in improving question formulation for some indicators. Studies of similar design in other low-income settings are needed to confirm these results.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Moçambique Inquérito Demográfico e de Saúde 2011 - Ministerio da Saude - MISAU/Moçambique; Instituto Nacional de Estatística - INE/Moçambique; ICF International (MISA/Moçambique, INE/Moçambique and ICF International, 2013)
O Inquérito Demográfico e de Saúde (IDS) em Moçambique faze parte dum programa internacional de inquéritos (MEASURE DHS) desenvolvido pelo ICF International através de um contrato com a USAID, com o propósito de apoiar aos governos e instituições privadas dos países em desenvolvimento na realização de inquéritos nacionais por amostragem, nas áreas de população e saúde. O Programa MEASURE DHS tem por objectivo: • Subsidiar a formulação de políticas e implementação de programas nas áreas de população e saúde; • Aumentar a base internacional de dados sobre população e saúde para acompanhamento e avaliação; • Aprimorar metodologia de inquérito por amostragem, e • Consolidar, na área de inquérito, a capacidade técnica da instituição executora no país participante do Programa. O Programa DHS teve início em 1984 e, desde então, já foram realizados inquéritos em mais de 70 países da América Latina, Caribe, África, Ásia e Leste Europeu.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

How active citizens can make a difference to improving service delivery in Mozambique: Phase 1: mapping citizen engagement programmes, initiatives and experiences - Programme, Citizen Engagement (2013)
The Citizen Engagement Program (CEP) supports citizens to monitor the quality of health and education service delivery in 4 of the 11 provinces of Mozambique, as well as to advocate for the improvement of the quality of those services at the district, provincial and national levels. The CEP aims at contributing towards the increased availability of relevant information for citizens to better access and benefit from services delivered by the public sector; improving citizens' capacity to assess service delivery and engage with service providers to improve the quality of health and education services at the primary and secondary levels; and supporting civil society organizations to leverage those findings within decision-making processes at higher levels. The programme will facilitate the dialogue between citizens / communities and service providers to improve the quality of services. The programme supports capacity-building, learning and experimentation, and will develop a robust system of monitoring and evaluation. The CEP will also analyse and build on experiences of service monitoring carried out by other actors and programmes, including other DFID and Irish Aid funded activities.
Accepted: 2017-12-05T13:07:47Z Publisher: (CEP) Citizen Engagement Programme / Cidadania e Participação
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; citizenship & participation / cidadania e participação; decentralization / descentralização; gender / género; health / saúde; ⛔ No DOI found

Juventude(s) e AIDS em Moçambique: Um Estudo Qualitativo no Distrito de Nhamatanda - Chicamisse, Francisco Armindo Zinhame (Universidade Federal de São Paulo, 2013)
O presente estudo pretende compreender como são desenvolvidas as ações de prevenção do HIV do Programa Geração Biz (PGB) direcionadas aos jovens dos 15-24 anos e, dessa forma buscar a compreensão da possível vulnerabilidade destes a infecção pelo HIV no distrito de Nhamatanda em Moçambique. Para o alcance deste desiderato baseei-me numa abordagem qualitativa, embasada no método etnográfico. No processo de coleta de dados privilegiei a observação participante, complementada por entrevistas semi-estruturadas e uma extensiva pesquisa bibliográfica. No distrito de Nhamatanda os jovens dos 15-24 anos constituem um dos segmentos populacionais mais afetados pelo HIV/AIDS, com uma taxa de prevalência estimada em 30,5% no ano de 2007, sendo por isso considerado um dos grupos mais vulneráveis a infecção pelo HIV. As ações de prevenção do HIV voltadas para este grupo são desenvolvidas pelo PGB, através das suas três componentes: escolar, comunitária e clínica. Entretanto, estas ações ainda estão assentadas na premissa de que a simples transmissão de informação implica na mudança de comportamentos dos jovens. Ademais, as ações de prevenção acabam tendo por vezes um caráter setorial e descontínuo, o que não permite o alcance de resultados mais duradouros no âmbito da prevenção do HIV. Os resultados deste estudo sugerem que as ações de prevenção do HIV ainda não se têm traduzido na redução considerável da referida vulnerabilidade dos jovens (15-24) a infecção pelo HIV neste distrito. Estas ações colocam por vezes os jovens em situações de maior suscetibilidade a infecção pelo HIV. Portanto, há uma necessidade de se repensar no modo como estas ações têm sido operacionalizadas, reelaborar os modelos pedagógicos que as norteiam e adequar os conteúdos semânticos das mensagens em função dos diferentes contextos socioculturais em que a epidemia se espraia.
Keywords: G - Mozambique / Moçambique; G - central / centro; GD - Nhamatanda; GP - Sofala; Health PEA; L - portuguese / português; access to services / acesso a serviços; health / saúde; youth / juventude

“Não basta introduzir reformas para se ter melhores serviços públicos”: subsídio para uma análise dos resultados das reformas no subsector de água rural em Moçambique - Forquilha, Salvador (Desafios para Moçambique 2013, 2013)
Em Setembro de 2012, o Governo de Moçambique anunciou a mudança de critérios para o cálculo das taxas de cobertura de abastecimento de água nas zonas rurais. Com efeito, de 500 pessoas para um poço ou furo equipado com uma bomba manual, num raio de 500 metros, passou -se para 300 pessoas para um poço ou furo equipado com uma bomba manual. Esta mudança de critérios acontece mais de 15 anos depois da aprovação da Política Nacional de Águas (PNA) e resulta da constatação de que, em muitos casos, os números oficiais estão longe de reflectir o que realmente se passa no terreno em termos de taxas de cobertura. Uma das consequências imediatas desta medida é, provavelmente, a revisão em baixa das taxas de cobertura de abastecimento de água rural, o que vai reforçar a ideia de que, à semelhança do que acontece com outros serviços públicos, o abastecimento de água rural ainda está longe de satisfazer as reais necessidades das populações.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; health - WASH / saúde - água; higiene e saneamento; rural development / desenvolvimento rural; ⛔ No DOI found

Saúde Para O Povo? Para Um Entendimento Da Economia Política E Das Dinâmicas Da Descentralização No Sector Da Saúde Em Moçambique - Weimer, Bernhard (Moçambique: Descentralizar o Centralismo? Economia Política, Recursos E Resultados, 2012)
Houve em 2011 três acontecimentos que revelaram as dimensões dos desafios que se colocam à gestão do Sistema Nacional de Saúde moçambicano em geral e ao Ministério de Saúde (MISAU) em particular. O primeiro foi uma auditoria externa das contas de 2009 do PROSAUDE II e do Fundo Global, realizada pela empresa de auditoria KPMG e entregue ao governo e aos seus parceiros internacionais em Junho de 2011. Esta auditoria revelou fraquezas consideráveis, nomeadamente em relação à auditoria interna e uma substancial diferença final não reconciliada entre os valores recebidos e os pagamentos efectuados. O segundo foi a crise de abastecimento de medicamentos, amplamente divulgada dos produtos farmacêuticos, quando os meios de comunicação noticiaram, num período de Março a Julho, que, no armazém farmacêutico central do MISAU, o CMAM,49 em Maputo, havia medicamentos no valor de pelo menos 2 milhões de USD que estavam fora de prazo; que os medicamentos se tinham esgotado nos hospitais públicos na Zambézia; e que grandes quantidades de medicamentos tinham desaparecido da farmácia do Hospital Central de Nampula.50 Os doadores recusaram um pedido de um montante adicional de 25 milhões de dólares para reabastecimento de medicamentos, feito pelo Ministro da Saúde em Março de 2011, argumentando que o governo teria que abordar e resolver as questões pendentes dos resultados da auditoria de 2009, antes de os doadores do PROSAUDE assumirem quaisquer compromissos de financiamento adicionais.51 Em terceiro lugar, pouco antes do fim do ano, o pessoal da saúde na Cidade de Nampula, incluindo os médicos, ameaçaram fazer greve, se não lhes fossem pagos os salários, três meses atrasados. Estes acontecimentos põem em relevo, em síntese, alguns dos principais desafios com que a gestão do sector da saúde se debate em Moçambique. Não se sabe até que ponto estes acontecimentos e o que eles revelam sobre a gestão de recursos no sector da saúde afectaram o funcionamento das unidades de saúde nas províncias e distritos, e o impacto sobre a saúde das pessoas doentes e da população em geral. Estas unidades dependem crucialmente de recursos (pessoal, financiamento e medicamentos) para o cumprimento da sua missão de controlar a doença e salvar vidas humanas, ou seja, para produzir os resultados de saúde que lhes compete alcançar, muitas vezes medidos com o indicador DALY.52 Neste artigo, não tentaremos avaliar o impacto das práticas de gestão no sector da saúde e os seus resultados em termos de vidas humanas. Tentaremos antes entender as dinâmicas políticas, económicas e institucionais que influenciam os resultados de saúde e o desempenho das unidades de saúde ao nível subnacional em Moçambique. O nosso argumento é que estas variáveis são determinadas não apenas por factores endógenos ao sector de saúde, como sejam as suas políticas e quadro regulamentar, a sua estrutura institucional, o grau de descentralização, e ainda os recursos que lhe são atribuídos e as suas capacidades de gestão. Também há factoresexógenos, como as decisões orçamentais do Ministério das Finanças, a Ajuda ao Desenvolvimento da Saúde (ADS)53 por parte dos doadores e as suas políticas e mecanismos de atribuição de fundos, como a abordagem sectorial integrada (SWAp)54 e o financiamento conjunto, bem como a mudança social e económica e as formas de governar um país, que produzem impactos decisivos no sistema de saúde e nos seus resultados. No que diz respeito à temática da descentralização da saúde, partimos, em primeiro lugar, do princípio que os ‘objectivos gerais da descentralização e a abordagem sectorial não são incompatíveis’, uma vez que tanto os primeiros como a segunda ‘têm por objectivo aumentar a eficiência técnica; incentivam uma maior participação; e põem a tónica na transparência e prestação de contas’ (Hutton, 2002: 3. Original em inglês). Em segundo lugar, chamamos a atenção para a necessidade de reconhecer um papel forte e normativo do Estado central nas políticas de saúde, na sua gestão, supervisão e questões de equilíbrio social, especialmente em matéria de cuidados de saúde primários, uma vez que a descentralização pode levar à diferenciação e à diversidade e não ao reforço da justiça social nos padrões e no acesso às unidades de saúde (Collins & Green, 1994). Como Booth sugeriu, o papel do Estado central é fundamental, nomeadamente em institucionalizar e supervisionar, do topo para a base, a disciplina de desempenho eficaz na componente de recursos humanos e na produção de serviços de qualidade a nível local (Booth, 2010: 34). Para este artigo, optámos por usar um quadro da análise político-económica para examinar alguns dos determinantes endógenos e exógenos. Do ponto de vista conceptual, a análise da economia política e da descentralização no sector da saúde pode ser estruturada de várias maneiras. Uma, é analisando as mudanças de epidemiologia, de características biomédicas dos corpos humanos e de ocorrênciaschave nos ciclos da vida humana (por exemplo, a fertilidade, a morbilidade ou mortalidade) como resultantes de intervenções por parte das instituições do sector da saúde, em condições sociais, económicas, ambientais e culturais em mudança. Esta abordagem é muitas vezes centrada na pobreza e assenta no pressuposto de que as mudanças institucionais, como a descentralização da prestação de serviços de saúde, conduzem a um aumento do bem-estar e a uma melhoria da saúde nas sociedades, se as intervenções institucionais (planos, programas, prestadores de serviços, etc.) forem ‘correctos’ e dispuserem de suficientes recursos financeiros e humanos, e capacidades, bem como de um quadro adequado de políticas. Dessa forma, julga-se que as taxas de fertilidade e mortalidade acabarão por diminuir, que as doenças infecciosas serão controladas e podem ser alcançados outros progressos no combate à pobreza e à doença (O’ Laughlin, 2010: 7).
Keywords: G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; health / saúde

Promoting Respectful Maternity Care in Mozambique - Reis, Veronica (USAID, 2012)
The objective of this document is to share the results of work undertaken in Mozambique to promote respectful health care, particularly in maternal and neonatal care. With its origins in “humanization of care” efforts in Latin America, this approach centers on the woman and her family and is grounded by principles of ethics and respect for human rights. The approach recognizes a client’s cultural background, and views the client as a person with values and expectations that should be respected during the provision of health care. Respectful maternity care (RMC) emphasizes the fundamental rights of the mother, newborn, and family, and recognizes that childbirth is a deeply personal experience for each woman and her family. In addition, RMC ensures that the client has timely access to health information, privacy, and evidence-based care. Promoting RMC can result in many benefits, including increased service utilization and better health outcomes. It is known that women refuse care from health providers who treat them poorly, even if these providers are capable of preventing or managing obstetric or newborn complications. In countries where a large proportion of births occur outside health facilities, RMC can contribute to increased uptake of maternal and newborn health (MNH) services.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Political economy of the health sector in Mozambique: Towards an understanding of its features, dynamics and challenges - MAP Consult (2012)
The powerpoint has the same objective as the article (see related section). ——- The present study was commissioned by the Department for International Development (DFID) in Mozambique. As a piece of independent research on the political economy of the health sector, it is considered to inform DFID’s health sector support programme for the period 2012-2016 and to lead to more in-depth inquiries of Mozambique’s health sector. The latter has witnessed a number of institutional, management, financial and governance challenges in the past few years, including a change in leadership considered important for the sector. The objective of this consultancy is to inform the development of a health sector support programme for the Government of Mozambique and to highlight particular political economy challenges and opportunities that DFID Mozambique should take into account in supporting PROSAUDE.
Keywords: *non-public; G - Mozambique / Moçambique; Health PEA; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; health / saúde

A systematic review of collaboration and network research in the public affairs literature: implications for public health practice and research - Varda, Danielle; Shoup, Jo Ann; Miller, Sara (American journal of public health, 2012)
OBJECTIVES: We explored and analyzed how findings from public affairs research can inform public health research and practice, specifically in the area of interorganizational collaboration, one of the most promising practice-based approaches in the public health field. METHODS: We conducted a systematic review of the public affairs literature by following a grounded theory approach. We coded 151 articles for demographics and empirical findings (n = 258). RESULTS: Three primary findings stand out in the public affairs literature: network structure affects governance, management strategies exist for administrators, and collaboration can be linked to outcomes. These findings are linked to priorities in public health practice. CONCLUSIONS: Overall, we found that public affairs has a long and rich history of research in collaborations that offers unique organizational theory and management tools to public health practitioners.
Edition: 2011/11/28 Publisher: American Public Health Association
Keywords: L - english / inglês; collaboration / colaboração; health / saúde

Political economy of the health sector in Mozambique: Towards an understanding of its features, dynamics and challenges - Weimer, Bernhard; Cumbi, Amelia J.; Macuane, José Jaime (MAP Consult, 2012)
The present study was commissioned by the Department for International Development (DFID) in Mozambique. As a piece of independent research on the political economy of the health sector, it is considered to inform DFID’s health sector support programme for the period 2012-2016 and to lead to more in-depth inquiries of Mozambique’s health sector. The latter has witnessed a number of institutional, management, financial and governance challenges in the past few years, including a change in leadership considered important for the sector. The objective of this consultancy is to inform the development of a health sector support programme for the Government of Mozambique and to highlight particular political economy challenges and opportunities that DFID Mozambique should take into account in supporting PROSAUDE.
Keywords: *non-public; *tagged; G - Mozambique / Moçambique; L - english / inglês; decentralization / descentralização; health / saúde

Effects of food price shocks on child malnutrition: the Mozambican experience 2008/09 - Arndt, Channing; Hussain, M. Azhar; Østerdal, Lars Peter (World Institute for Development Economics Research (WIDER), 2012)
A propitiously timed household survey carried out in Mozambique over the period 2008-09 permits us to evaluate the short-to-medium run relationship between sudden shocks to food prices and child nutrition status. We link local price inflation with child malnutrition status. We find that the prevalence of underweight amongst children rises in response to a higher inflation rate for basic food products. Stunting and wasting malnutrition measures are mostly insensitive to the inflation rate. The very high food inflation during 2008/09 was responsible for an extra 39,000 moderately underweight and 24,000 severely underweight children.
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde

Abastecimento De Água Nas Zonas Rurais: Avaliação Dos Progressos Para a Prestação De Serviços Sustentáveis - Munguambe, Carlos Gideon José; Jesus, Vitória Afonso Langa de (IRC International Water and Sanitation Centre, 2011)
This study presents an analytical ‘picture’ of the rural water sub-sector in Mozambique, describing the legal framework, mechanisms for coordination, harmonisation, funding, accountability, participation and supervision. The study was commissioned for the Sustainable Services at Scale, or Triple-S, initiative, which aims to contribute to improving the sustainability of global rural water supply. According to the general population census carried out in 2007, Mozambique had a total population of 20,226,296, 70.2% of whom live in rural areas, with a water coverage rate of only 54%.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; decentralization / descentralização; health - WASH / saúde - água; higiene e saneamento; health / saúde

Health Commodity Security Project - World Bank (World Bank, 2010)
Information document about the Health Commodity Security Project. It is divided in the sections below: - Country and Sector Background - Objectives - Rationale for Bank Involvement - Description - Financing - Implementation - Sustainability - Lessons Learned from Past Operations in the Country/Sector - Safeguard Policies (including public consultation) - List of Factual Technical Documents - Contact point - For more information contact
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; health / saúde

“All I Eat Is ARVs:” The Paradox of AIDS Treatment Interventions in Central Mozambique - Kalofonos, Ippolytos Andreas (Medical Anthropology Quarterly, 2010)
The number of people on antiretroviral treatment in Mozambique has increased by over 1,500 percent since it first became free and publicly available in 2004. The rising count of “lives saved” seems to portray a success story of high-tech treatment being provided in one of the poorest contexts in the world, as people with AIDS experience dramatic recoveries and live longer. The “scale-up” has had significant social effects, however, as it unfolds in a region with a complicated history and persistent problems related to poverty. Hunger is the principal complaint of people on antiretroviral treatment. The inability of current interventions to adequately address this issue leads to intense competition among people living with HIV/AIDS for the scarce resources available, undermining social solidarity and the potential for further community action around HIV/AIDS issues. Discourses of hunger serve as a critique of these shortcomings, and of the wider political economy underlying the HIV/AIDS epidemic.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - central / centro; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde